1995
DOI: 10.1103/physrevd.51.4623
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic evidence for top quark pair production inW+multijet events inpp¯collisions at √s=1.8 TeV

Abstract: We present a study of W +multijet events that compares the kinematics of the observed events with expectations from direct QCD W +jet production and from production and decay of top quark pairs. The data were collected in the 1992-93 run with the Collider Detector at Fermilab (CDF) from 19.3 pb −1 of proton-antiproton collisions at √ s = 1.8 TeV. A W + ≥ 2 jet sample and a W + ≥ 3 jet sample are selected with the requirement that at least the two or three jets have energy transverse with respect to the beam ax… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…However, the theory suggested that the bottom quark should have an SU (2) partner named top. The CDF and D∅ collaborations at Fermilab began a top quark search that came to a successful conclusion in February 6 1995 [3,4,5]. Since then, the study of the top quark has been a primary focus of both experiments.…”
Section: Top Quarkmentioning
confidence: 99%
“…However, the theory suggested that the bottom quark should have an SU (2) partner named top. The CDF and D∅ collaborations at Fermilab began a top quark search that came to a successful conclusion in February 6 1995 [3,4,5]. Since then, the study of the top quark has been a primary focus of both experiments.…”
Section: Top Quarkmentioning
confidence: 99%
“…The variable cos ? has been shown [27] to have discriminating power against the background, and we use here the quantity E ? T E T sin 2 ?…”
Section: Neural-network-based Kinematical Selectionmentioning
confidence: 99%
“…MRST72: PDF from MRST group [72] with the same QCD scale as CTEQ5L MRST75: Same as MRST72 but with a different Λ 11 10 This indicates that our method is insensitive to initial state radiation 11 MRST75 is generated with Λ = 300 M eV , while MRST72 with Λ = 228 M eV These uncertainties are estimated by the "re-weighting method" [75]: a PDFdependent relative weight to CTEQ5L…”
Section: Qcd Scale (λ)mentioning
confidence: 99%
“…First of all the renormalizability of the standard model requires that the sum of electric charges of all left-handed fermions is zero. The discovery of top quark was accomplished in 1995 at the CDF and D/ 0 experiment [10,11]. After more than 10 years from its discovery the world average for top quark mass is M top = 170.9 ± 1.1(stat) ± 1.5(syst)GeV /c 2 [59] (more than 30 times the mass of second heaviest quark).…”
Section: The Top Quarkmentioning
confidence: 99%
See 1 more Smart Citation